Integrin Regulated Autoimmune Disorders: Understanding the Role of Mechanical Force in Autoimmunity - Banerjee, Souradeep; Nara, Ritika; Chakraborty, Soham; Chowdhury, Debojyoti; Haldar, Shubhasis (Frontiers in Cell and Developmental Biology, 2022)
Pathophysiology of autoimmune disorders are multifactorial, where immune cell migration, adhesion, and lymphocyte activation play crucial roles in its progression. These immune processes are majorly regulated by adhesion molecules at cell¬¬¬¬¬-extracellular matrix (ECM) and cell-cell junctions. Integrin, a transmembrane focal adhesion protein, plays an indispensable role in these immune cell mechanisms. Notably, integrin is regulated by mechanical force and exhibit bidirectional force transmission from both the ECM and cytosol, regulating the immune processes. Recently, integrin mechanosensitivity has been reported in different immune cell processes; however, the underlying mechanics of these integrin mediated mechanical processes in autoimmunity still remains elusive. In this review, we have discussed how integrin-mediated mechanotransduction could be a linchpin factor in the causation and progression of autoimmune disorders. We have provided an insight on how tissue stiffness exhibits a positive correlation with the autoimmune diseases’ prevalence. This provides a plausible connection between mechanical load and autoimmunity. Overall, gaining insight into the role of mechanical force in diverse immune cell processes and their dysregulation during the autoimmune disorders will open a new horizon to understand this physiological anomaly.